HUBUNGAN KARAKTERISTIK IBU, PELAKSANAAN KELUARGA SADAR GIZI (KADARZI) DAN PERILAKU HIDUP BERSIH SEHAT (PHBS) DENGAN KEJADIAN STUNTING (Studi kasus pada baduta 6 - 23 bulan di Wilayah Kerja Puskesmas Pucang Sawit Kota Surakarta) - Apriani, Lina (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Background: Stunting problems in toddlers is still a special concern in the world. Implementation of low levels of kadarzi and phbs is one of the causes of stunting in infants.Objective: The purpose of this research is to analyze the relationship of mother characteristics, the implementation of kadarzi and PHBS ‘Pure’ with the stunting incident in baduta 6-23 months.Method: The type of research used is analytic observational with cross sectional approach. The population of this study was the 1044 baduta 6 – 23 months and the sample of this study were 35 baduta 6 - 23 months by using sampling technique with simple random sampling. Data analysis using Chi-Square.Result: The results of the study most of the mothers have advanced education (65.7%), working status (71.4%), family income> UMR (62.9%) and stunting baduta (34.3%). Implementation of less good kadarzi (54,3%) and implementation of PHBS ‘Pure’ is poor (51.4%) and the least-implemented indicators of the family are physical activity (20%), non-smoking (28.6%) and no garbage (60%).Conclusion: There is relationship of mother characteristic with stunting baduta (p=0,001) that is mother education level and family income level. There is no relation between mother's job status and stunting (p=0,735). There is a negative relationship between the implementation of kadarzi and the stunting baduta (p = 0,001, C = 0,568) and there is a negative relationship between the implementation of 'Pure' PHBS with stunting baduta (p = 0,001, C = 0,575).